2021
DOI: 10.1111/ajad.13137
|View full text |Cite
|
Sign up to set email alerts
|

Demographic, Behavioral, and Proximal Risk Factors for Gambling Disorder in the US Military

Abstract: Background and Objectives To estimate the diagnostic prevalence and incidence of gambling disorder among United States service members and to identify associated risk factors, including demographics, history of mental illness or substance misuse, and proximity to legalized gambling vicinities. Methods Gambling disorder cases comprised active component Service members who received a pathological or problem gambling diagnosis between October 1, 2005 and September 30, 2015. There were 901 cases (392 incidents) du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…However, while costs may increase for those identified with mental health conditions, there is an obvious trade-off in the costs saved from future healthcare resource use as well as criminal justice contact and accrued debt. Notwithstanding the absence of standardised screening tools for problem gambling risk in the military, our findings indicate that engaging all healthcare professionals working with veterans as part of support for other, comorbid difficulties such as mental health problems and alcohol and substance use is needed to better understand the trajectory of gambling-related harms 6 34…”
Section: Discussionmentioning
confidence: 96%
“…However, while costs may increase for those identified with mental health conditions, there is an obvious trade-off in the costs saved from future healthcare resource use as well as criminal justice contact and accrued debt. Notwithstanding the absence of standardised screening tools for problem gambling risk in the military, our findings indicate that engaging all healthcare professionals working with veterans as part of support for other, comorbid difficulties such as mental health problems and alcohol and substance use is needed to better understand the trajectory of gambling-related harms 6 34…”
Section: Discussionmentioning
confidence: 96%
“…Disordered gambling in the military is under-researched compared with other mental health difficulties (Etuk et al, 2020 ), despite the likelihood of developing GD being higher among the military compared to the general population (van der Maas & Nower, 2021 ). Estimates of the prevalence of sub-threshold GD or ‘problem gambling’ suggest military status may be a significant risk factor (Garvey Wilson et al, 2021 ). Roberts et al ( 2020 ) found UK veterans were eight times more likely to meet problematic gambling criteria compared to an age/gender-matched general population sample.…”
Section: Introductionmentioning
confidence: 99%